A first report on the isolation and characterization of a highly potential indigenous mosquitocidal bacterium (Bacillus thuringiensis subspecies Israelensis VCRC B647) from red soil, India - Bhagyashree Bora; Jibi Lukose; Kakhuangailiu Gangmei; Manikandan Sivaprakasam; Abhisubesh Vijayakumar; Sahadiya Mandodan; Hemaladkshmi Padmanaban; Aneha Kunnikuruvan; Mathivanan Ashokkumar; Vijayalakshmi Krishnamoorthy; Poopathi Subbiah (Wolters Kluwer Medknow Publications, 2024)
Background: To control mosquito vectors causing human diseases, bacterial biopesticides are currently in use. Indeed, the recent development of resistance to these bacterial agents has impeded its applications. Under these circumstances, the search for novel bacterial agents with mosquitocidal activity is unavoidable. In this study, a novel mosquitocidal bacterium was isolated from red soils of agricultural field. Objectives: The objective of this study was to isolate and identify new mosquitocidal bacteria from the natural environment. Materials and Methods: Soil samples were collected during 2021-2022 from Tirupathur district of Tamil Nadu, South India. The samples were bioprocessed for culturing the bacterial colony in a suitable culture medium (Nutrient Yeast Salt Medium), and after 72 h, the bacterial cell mass was removed and lyophilized. Bioassays (mosquito toxicity assays) were carried out to screen the bacterial colonies for mosquitocidal effect. The potential colony was further analyzed, and identified for its application in mosquito control. Results: The new isolate screened from red soil was identified as Bacillus thuringiensis subspecies israelensis (VCRC B647) as per the ilvD gene sequence analysis. The strain was found to be potentially effective in controlling mosquito larvae, and further biochemical analyses, bacterial growth, biomass, and protein content were investigated. The new isolate did not show any toxic effect on nontarget aquatic organisms. Conclusion: It is significant to depict that the mosquitocidal action of this new isolate (Bti) is highly significant than the reference strain of Bti-H14. It is concluded that this is the first report that an indigenous strain of Bti VCRC B647 is very effective in mosquito control.